2018
DOI: 10.7567/jjap.57.126101
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic electron energy gain in inductively coupled magnetized plasmas accompanying electron reflection at chamber wall

Abstract: Single-electron motions near the chamber wall of a type of inductively coupled magnetized plasmas were analyzed using a Monte Carlo method to understand the mechanism of electron energy gain (EEG). The analysis revealed a counterintuitive mechanism that electron reflection promotes the EEG in the presence of E × B drifts and collisional scattering. Distributions of EEG, energy loss, and mean electron energy were calculated using a simplified flat wall model at various strengths of electric and magnetic fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In previous work dealing with the QMF or the CDMFs, the equi-strength contours of B DC = 1B ECR and 2B ECR have often been shown as a measure. Such contours have been referred to in demonstrations of the partial resonance and the resulting EEG in relation to the ECR, 11,18,[22][23][24] or to indicate the electron confinement region 25) and a rough boundary around which the electron motion changes from meandering to gyration. 2),26)-28)) The present resonant region is set with widths of ±0.5B ECR for both sides of B DC = B ECR .…”
Section: Coils and Magnetic Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work dealing with the QMF or the CDMFs, the equi-strength contours of B DC = 1B ECR and 2B ECR have often been shown as a measure. Such contours have been referred to in demonstrations of the partial resonance and the resulting EEG in relation to the ECR, 11,18,[22][23][24] or to indicate the electron confinement region 25) and a rough boundary around which the electron motion changes from meandering to gyration. 2),26)-28)) The present resonant region is set with widths of ±0.5B ECR for both sides of B DC = B ECR .…”
Section: Coils and Magnetic Fieldsmentioning
confidence: 99%
“…The high EEG near the RF antenna is due to high electric field. On the high EEG near the sidewall, it has been reported that the directionality of the azimuthal electron drift caused by the electron reflection at the sidewall contributes to the EEG stochastically, 18) and the EEG is enhanced in the presence of the sheath electric field. 33) As R A increases, the amount of energy supplied to electrons in the chamber increases, the region of high EEG becomes wider, and the EEG in the resonant region tends to increase.…”
Section: Dependence Of Eeg On Electric Field Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motion of an electron close to the chamber wall in a magnetized ICP was analyzed, and a counterintuitive mechanism of electron reflection was revealed. 80) Lorentz force along the RF electric field induced electron motions parallel to the sidewall. The behavior of the majority of electrons was determined by individual electrons that gained energy stochastically.…”
Section: 5mentioning
confidence: 99%
“…The authors have analyzed fundamental structure and response of an ICP under the CDMFs, so-called the X-point plasmas developed as an ion source, [17][18][19][20] and it was reported that high energy deposition efficiency was observed in three characteristic regions. [21][22][23][24] The high efficiencies in the three regions were attributed to high electric fields under the RF antenna, the partial resonance 25,26) around the region of the RF-resonant magnetic field strength, 27) and a stochastic heating particular to the region near the sidewall. 24) The power deposition to electrons near the sidewall was indicated to occur in non-magnetized ICPs as well by high ionization rates and high number densities of excited particles observed there.…”
Section: Introductionmentioning
confidence: 99%